1994
DOI: 10.1002/job.4030150403
|View full text |Cite
|
Sign up to set email alerts
|

The boundaryless career: A competency‐based perspective

Abstract: This paper proposes a competency-based view of careers, derived from competencybased models of employcr firms. The implications for boundaryless careers are cxplored by reference to changing organizational. occupational and industry community contexts. All of these contexts are seen as likely to promote boundaryless career behaviors. Future research possibilities for each of three career competencies, and for interdependence among the competencies. are briefly examined.We are indebted to Suzyn Ornstein, Denise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
911
2
59

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 896 publications
(991 citation statements)
references
References 39 publications
(19 reference statements)
19
911
2
59
Order By: Relevance
“…A body of research has confirmed that career capital comprises of three dimensions of knowing (Suutari & Mäkelä, 2007;Dickmann & Harris, 2005;Inkson & Arthur, 2001) originally defined by DeFillippi and Arthur (1994) as knowing whom, knowing why and knowing how. Knowing whom consists of social relations within and external to the organisation and within a professional network that is relevant to the career (DeFillippi & Arthur, 1994). Knowing how represents work related skills, knowledge and competencies (DeFillippi & Arthur, 1994;Dickmann & Harris, 2005).…”
Section: The Components Of Knowledge Workers' Career Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…A body of research has confirmed that career capital comprises of three dimensions of knowing (Suutari & Mäkelä, 2007;Dickmann & Harris, 2005;Inkson & Arthur, 2001) originally defined by DeFillippi and Arthur (1994) as knowing whom, knowing why and knowing how. Knowing whom consists of social relations within and external to the organisation and within a professional network that is relevant to the career (DeFillippi & Arthur, 1994). Knowing how represents work related skills, knowledge and competencies (DeFillippi & Arthur, 1994;Dickmann & Harris, 2005).…”
Section: The Components Of Knowledge Workers' Career Capitalmentioning
confidence: 99%
“…Knowing whom consists of social relations within and external to the organisation and within a professional network that is relevant to the career (DeFillippi & Arthur, 1994). Knowing how represents work related skills, knowledge and competencies (DeFillippi & Arthur, 1994;Dickmann & Harris, 2005). Knowing why relates to the individual's identity, career related choices and the motivation and energy the individual brings to their careers (DeFillippi & Arthur, 1994;Inkson & Arthur, 2001).…”
Section: The Components Of Knowledge Workers' Career Capitalmentioning
confidence: 99%
“…This interest in career selfmanagement accentuates the importance of learning emphasized in recent years. Acquiring knowledge and skills (through learning) often benefits one's career (DeFillippi & Arthur, 1994) because it is a form of human capital investment that is likely to be rewarded in the labor market, for example, through higher salary or more promotions (Ng, Eby, Sorensen, & Feldman, 2005). Organizations can provide employees with a variety of channels for learning, including formal training and development programs, workshops, informal sharing groups, mentoring, job rotations, international assignments, promotions, and demotions (e.g., Stilwell, Liden, Parsons, & Deconinck, 1998).…”
Section: Opportunity For Learningmentioning
confidence: 99%
“…However, others suggested that having networks in one fi eld did not support exploration of another. This fi nding is important as it suggests that while Defi llippi and Arthur's (1996) notion of knowing whom competencies is important, it has only limited value for career exploration -especially if exploration transcends professional boundaries.…”
Section: Outplacement Servicesmentioning
confidence: 99%